The Influence of Green Human Resources Management and Sustainable Environment on Organizational Performance Mediated by Corporate Social Responsibility - Syamsunasir Syamsunasir; Dewi Puspaningtyas Faeni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine the influence of Green Human Resources Management (GHRM) and Sustainable Environment on corporate social responsibility (CSR) -mediated organizational performance at financial industries. This study uses a descriptive statistical design with a quantitative approach. The population in this study is 400 employees of financial industries. The data used in this study used primary data collected directly from respondents through questionnaires and interviews with interviews. Sampling was done using the non-probability sampling method. After the calculation of the Slovin Formula, a minimum sample size of 80 employees/sample was obtained. This study uses descriptive statistical analysis methods, verifier analysis, data quality tests that include validity and reliability, hypothesis tests that include F and t tests, and determination coefficient tests that are processed using Smart PLS 4.0 software. The results show that GHRM has a positive and significant influence on organizational performance through CSR mediation, sustainable environment has a significant positive influence on organizational performance through CSR mediation, GHRM relationships mediated by CSR have a significant influence on organizational performance, sustainable environment relationships mediated by CSR are not significant on organizational performance, GHRM has a direct, negative and insignificant influence on organizational performance, and sustainable environment has a direct positive but not significant influence on organizational performance.